A Study on Moslem Behavior Toward Khutbat Al-Jum'a - Mabaroh, Barotun (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
This paper is derived from the result of the researcher’s ethnographic research. It contains a description of moslem behavior in folllowing Khutbat Al-Jum'a in Jumu’ah prayer. It discusses moslem viewpoints, customs, needs, and beliefs toward Khutbat Al-Jum'a presentation. It aims at giving ‘a potrait’ of a particular moslem culture on the Islamic practices. In collecting the data, the researcher used some instruments through some ways. The researcher was the main (human) instrument in this research. In addition, the researcher used interview guideline for obtaining data about the viewpoints, customs, needs, and beliefs toward Khutbat Al-Jum'a in Jumu’ah prayer participants.  Furthermore, the researcher employed field-notes while she was obeserving the practice of Khutbat Al-Jum'a in Jumu’ah prayer.  Last, the researcher documented the process of Khutbat Al-Jum'a presentation using camera. Finally, it resulted  a developing theoretical ideas from the frame description and contributed to a refinement and betterment on Khutbat Al-Jum'a presentation.